Solid electrolyte and electrode mixture using the same, solid electrolyte layer, solid-state battery

By controlling the ore ratio of sulfur and silver germanium and lattice distortion, the lithium ion conductivity in solid electrolytes is improved, and the problem of insufficient lithium ion conductivity in the prior art is solved, and a solid-state battery with high energy density and safety is realized.

CN114556655BActive Publication Date: 2025-02-28MITSUI MINING & SMELTING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080072393.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-29
Filing Date
2020-10-20
Publication Date
2025-02-28
Estimated Expiration
2040-10-20

AI Technical Summary

Technical Problem

The prior art is difficult to improve the sulfosil silver germanium ore ratio and lithium ion conductivity, and there is a lack of effective methods to control the lithium ion conductivity in solid electrolytes.

Method used

By controlling the sulphur silver germanium ore ratio and the lattice distortion of compound A in the solid electrolyte, the lithium ion conductivity is improved by combining specific raw material mixing and calcining conditions.

Benefits of technology

The high lithium ion conductivity of solid electrolytes is achieved, and the lithium ion conductivity reaches more than 4.0mS/cm, which significantly improves the energy density and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003596709720000141
    Figure BDA0003596709720000141
Patent Text Reader

Abstract

The solid electrolyte of the present invention contains the following compound: the compound includes a crystalline phase having an argyrodite-type crystal structure, and Li a PS b X c (X is at least one halogen element. a represents a number greater than 3.0 and less than 6.0. b represents a number greater than 3.5 and less than 4.8. c represents a number greater than 0.1 and less than 3.0). The ratio of the crystalline phase of the argyrodite structure to the total crystalline phase constituting the aforementioned solid electrolyte is greater than 97.0wt%. The lattice distortion of the aforementioned compound is less than 0.10%. It is suitable that the lithium ion conductivity of the aforementioned solid electrolyte is greater than 4.0mS / cm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolyte and an electrode mixture, a solid electrolyte layer and a solid-state battery using the same. Background Art

[0002] In recent years, solid electrolytes have attracted attention as an alternative to electrolyte solutions used in various liquid batteries. Solid-state batteries using such solid electrolytes are expected to be put into practical use as batteries that are safer and have higher energy density than liquid batteries using flammable organic solvents.

[0003] As the prior art related to the solid electrolyte, for example, the techniques described in Patent Documents 1 and 2 are known. Patent Document 1 describes a sulfide solid electrolyte having a composition formula of Li 7-x PS 6-x Ha x (Ha represents Cl or Br) and has a cubic crystal structure of space group F-43m. Patent document 2 describes a sulfide solid electrolyte comprising a argyrodite-type crystal structure and Li 7-x-2y PS 6-x-y Cl x Represents the compound.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent document 1: US2016 / 156064A1

[0007] Patent document 2: US2017 / 222257A1 Summary of the invention

[0008] One of the properties required of solid electrolytes is high lithium ion conductivity. In order to improve lithium ion conductivity, it can be considered, for example, to control the argyrodite rate to be higher in the techniques described in the above-mentioned patent documents 1 and 2. However, these documents do not disclose a specific method for improving the argyrodite rate. In addition, these documents do not specifically mention other factors for improving lithium ion conductivity. Therefore, the subject of the present invention is to provide a solid electrolyte with high lithium ion conductivity.

[0009] The present invention provides a solid electrolyte, which contains the following compound: the compound contains a crystalline phase having an argyrodite-type crystal structure, and is formed by Li a PS b X c (X is at least one halogen element. a represents a number greater than or equal to 3.0 and less than or equal to 6.0. b represents a number greater than or equal to 3.5 and less than or equal to 4.8. c represents a number greater than or equal to 0.1 and less than or equal to 3.0) represents,

[0010] The ratio of the crystalline phase having the argyrodite type crystal structure to the total crystalline phase constituting the solid electrolyte is 97 wt % or more,

[0011] The lattice distortion of the aforementioned compound is less than 0.10%. DETAILED DESCRIPTION

[0012] Hereinafter, the present invention will be described based on its preferred embodiments. The solid electrolyte of the present invention comprises Li a PS b X c (X is at least one halogen element. a represents a number greater than 3.0 and less than 6.0. b represents a number greater than 3.5 and less than 4.8. c represents a number greater than 0.1 and less than 3.0). The compound contains a crystalline phase having a argyrodite-type crystal structure. In addition, the compound is solid at room temperature (25°C) and has lithium ion conductivity. In the following description, for convenience, the compound is also referred to as "Compound A".

[0013] Compound A in the present invention is a crystalline material containing a crystalline phase having an argyrodite crystal structure. In particular, compound A may contain a glass component, i.e., an amorphous component. Compound A "containing a crystalline phase having an argyrodite crystal structure" means that as long as compound A contains at least a crystalline phase having an argyrodite crystal structure, it may also contain a crystalline phase different from the crystalline phase having the argyrodite crystal structure (also referred to as "heterophase"). Of course, the heterophase may not be contained.

[0014] The crystalline phase having an argyrodite structure refers to a crystalline phase possessed by a compound group having a mineral derived from the chemical formula Ag8GeS6. From the viewpoint of improving lithium ion conductivity, the aforementioned compound having a crystalline phase having an argyrodite structure preferably has a cubic crystal structure.

[0015] Whether the solid electrolyte of the present invention contains a compound having a crystalline phase of an argyrodite structure can be confirmed, for example, by XRD measurement. That is, in an X-ray diffraction pattern measured by an X-ray diffraction device using CuKα1 rays, the crystalline phase of the argyrodite structure has characteristic peaks at 2θ=15.34°±1.00°, 17.74°±1.00°, 25.19°±1.00°, 29.62°±1.00°, 30.97°±1.00°, 44.37°±1.00°, 47.22°±1.00°, and 51.70°±1.00°. Furthermore, for example, characteristic peaks are also present at 2θ=54.26°±1.00°, 58.35°±1.00°, 60.72°±1.00°, 61.50°±1.00°, 70.46°±1.00°, and 72.61°±1.00°. It should be noted that the "peak" in this specification refers to the apex of the peak. In addition, the above peaks preferably exist independently and do not overlap with other peaks.

[0016] In the solid electrolyte of the present invention, the crystalline phase of the argyrodite-type crystal structure constituting compound A preferably becomes the main phase relative to all crystalline phases. The main phase refers to: in the solid electrolyte of the present invention, the crystalline phase with the highest existence ratio based on the number of moles among all crystalline phases. The solid electrolyte of the present invention may be composed only of a crystalline phase having a argyrodite-type crystal structure, or, within the scope of not impairing the effect of the present invention, may further include a substance having a different phase from the crystalline phase having a argyrodite-type crystal structure. As such a heterogeneous substance, for example, lithium halides and Li3PS4 can be listed.

[0017] As described above, the solid electrolyte of the present invention contains compound A, and the compound A includes a crystalline phase having a argyrodite-type crystal structure, and the solid electrolyte further includes a phase different from the crystalline phase having the argyrodite-type crystal structure according to circumstances. In addition, one feature of the solid electrolyte of the present invention is that the argyrodite rate in the solid electrolyte is controlled. The argyrodite rate refers to: the mass ratio (wt%) of the crystalline phase of the argyrodite-type structure relative to the total crystalline phase constituting the solid electrolyte of the present invention. In addition, another feature of the solid electrolyte of the present invention is that the lattice distortion of the compound A contained in the solid electrolyte is controlled.

[0018] Specifically, the argyrodite ratio of the solid electrolyte of the present invention is controlled to be high, and the lattice distortion of compound A is controlled to be low. As a result, the lithium ion conductivity of the solid electrolyte of the present invention is improved. The present inventors believe that the reason is as follows.

[0019] The solid electrolyte of the present invention comprises compound A. It can be considered that: in the solid electrolyte comprising compound A, the higher the existence ratio of the crystalline phase having the argyrodite-type crystal structure, the higher the lithium ion conductivity of the solid electrolyte. However, it has been impossible to control the argyrodite rate in the solid electrolyte to a high value so far. In contrast, the inventors have found that: by using the method described below to manufacture a solid electrolyte, the argyrodite rate of the solid electrolyte can be controlled to a high value. Furthermore, the inventors have found that: by not only increasing the argyrodite rate of the solid electrolyte, but also controlling the lattice distortion of compound A to a small value, the lithium ion conductivity of the solid electrolyte can be further improved. Small lattice distortion means: in the crystal structure of compound A, atoms exist in appropriate positions. It can be considered that: as a result, lithium ions are easily and smoothly conducted in compound A, and the lithium ion conductivity of the solid electrolyte is improved.

[0020] From the viewpoint of making the above-mentioned advantageous effects more significant, it is preferred that the ratio of the crystalline phase having the argyrodite type crystal structure to the total crystalline phase constituting the solid electrolyte (hereinafter sometimes referred to as "argyrodite ratio") is, for example, 97.0 wt% or more, more preferably 97.2 wt% or more, and further preferably 97.4 wt% or more. The higher the argyrodite ratio, the more preferred it is, and the ideal is 100 wt%. The upper limit of the argyrodite ratio that can be achieved using the current technical level is about 98.6 wt%. If the argyrodite ratio is as high as this, the lithium ion conductivity of the solid electrolyte becomes sufficiently high.

[0021] From the same viewpoint as above, in the solid electrolyte of the present invention, it is preferred that the lattice distortion of the compound A contained in the solid electrolyte is less than 0.10%, more preferably less than 0.09%, and further preferably less than 0.08%. From the viewpoint of improving the lithium ion conductivity of the solid electrolyte, the smaller the lattice distortion of the compound A, the better. The lower limit of the lattice distortion that can be achieved using today's technical level is about 0.04%. By further reducing the lattice distortion of the compound A, the lithium ion conductivity of the solid electrolyte can be fully improved.

[0022] The specific method for measuring the argyrodite rate in the present invention is described in detail in the examples described below. In addition, the lattice distortion of the compound A contained in the solid electrolyte of the present invention can be determined by X-ray diffraction measurement. The specific method is described in detail in the examples described below.

[0023] The solid electrolyte of the present invention shows a high value of preferably 4.0 mS / cm or more, more preferably 4.5 mS / cm or more, further preferably 4.8 mS / cm or more, and further preferably 6.0 mS / cm or more in lithium ion conductivity at room temperature (25° C.) by controlling the argyrodite ratio of the solid electrolyte and the lattice distortion of compound A. The lithium ion conductivity of the solid electrolyte can be measured by the method described in the examples described below.

[0024] The compound A contained in the solid electrolyte of the present invention is as described above with Li a PS b X c Here, "compound A is Li a PS b X c "Indicates" means: including compound A becoming Li a PS b X c In the composition formula, a, which represents the molar ratio of the lithium (Li) element, is preferably a number greater than 3.0 and less than 6.0, more preferably a number greater than 3.2 and less than 5.8, and further preferably a number greater than 3.4 and less than 5.4. It should be noted that a may be less than 5.4.

[0025] In the above composition formula, b representing the molar ratio of sulfur (S) element is, for example, preferably 3.5 to 4.8, more preferably 3.8 to 4.6, and even more preferably 4.0 to 4.4. It should be noted that b may be less than 4.4.

[0026] Furthermore, in the above composition formula, c is preferably a number of 0.1 or more and 3.0 or less, more preferably a number of 0.2 or more and 2.5 or less, and further preferably a number of 0.4 or more and 2.0 or less. When a, b, and c are within this range, the lithium ion conductivity of the compound A becomes sufficiently high. In the above composition formula, X represents at least one halogen element. When X is one, the compound A may include Li a PS b F c , Li a PS b Cl c , Li a PS b Br c and Li a PS b I c When X is two, compound A is Li a PS b X 1 y X2 z Indicates. 1 and X 2 represents different halogen elements. In addition, y and z represent numbers that satisfy c=y+z and are greater than 0. 1 With X 2 For example, the combination of Cl and Br, the combination of Cl and I, and the combination of Br and I can be listed. When X is three types, compound A is Li a PS b X 1 y X 2 z X 3 v Indicates. 1 , X 2 and X 3 represents different halogen elements. In addition, y, z and v represent numbers that satisfy c=y+z+v and are greater than 0. 1 With X 2 With X 3 Examples of the combination of Cl, Br and I include a combination of Cl, Br and I. The solid electrolyte of the present invention may contain only one compound A or may contain two or more compounds A.

[0027] In the present invention, the feed amount is Li a PS b X c The compound A obtained in the manner may contain elements other than lithium (Li), phosphorus (P), sulfur (S) and halogen (X). For example, part of the lithium (Li) element may be replaced by other alkali metal elements, part of the phosphorus (P) element may be replaced by other nitrogen group elements, or part of the sulfur (S) element may be replaced by other chalcogen elements.

[0028] The solid electrolyte of the present invention may contain impurities in addition to compound A. From the viewpoint of minimizing the effect on performance, the impurity content may be less than 5 mol%, preferably less than 3 mol%, and particularly preferably less than 1 mol%.

[0029] When the solid electrolyte of the present invention contains only one compound A, the lattice distortion of the compound A preferably satisfies the above range. On the other hand, when the solid electrolyte of the present invention contains two or more compounds A, it is preferred that the lattice distortion of at least one compound A satisfies the above range, and it is preferred that the lattice distortion of all compounds A satisfies the above range.

[0030] From the viewpoint of suppressing the viscosity when preparing the slurry, the BET specific surface area of ​​the solid electrolyte of the present invention is preferably 12 m2 / g or less, more preferably 10m 2 / g or less, more preferably 8m 2 / g or less. From the perspective of suppressing viscosity when making slurry, the smaller the BET specific surface area, the better. However, if it is too small, there is a concern that the lithium ion conductivity will decrease due to the decrease in contact points. Therefore, if the BET specific surface area is 1.0m 2 / g or more, especially 1.5m 2 / g or more, especially 2.0m 2 / g, the reduction in lithium ion conductivity caused by the reduction in contact points can be fully suppressed, and it is also effective in suppressing the viscosity when making slurry. This range of BET specific surface area can be achieved, for example, by controlling the particle size of the solid electrolyte. The method for determining the BET specific surface area is described in detail in the examples described below.

[0031] The solid electrolyte includes a powder in the form of a particle assembly. The particle size of the solid electrolyte of the present invention is the volume cumulative particle size D when the cumulative volume is 50 volume % based on the laser diffraction scattering particle size distribution measurement method. 50 It is preferably 0.8 μm or more, preferably 0.9 μm or more, and particularly preferably 1.0 μm or more. 50 For example, it is preferably 15.0 μm or less, particularly preferably 10.0 μm or less, and particularly preferably 7.0 μm or less. 50 The above upper limit is provided, so that when the solid electrolyte of the present invention is used in combination with other solid electrolytes, there is an advantage that the solid electrolyte of the present invention can easily enter the gaps of the other solid electrolytes. As a result, the contact points and contact areas between the solid electrolytes are increased, and the lithium ion conductivity can be improved efficiently. On the other hand, by making the volume cumulative particle size D of the solid electrolyte of the present invention 50 By having the above lower limit, it is possible to suppress excessive lattice distortion of compound A. In addition, it is possible to suppress an increase in the surface area of ​​the entire solid electrolyte powder, thereby suppressing the occurrence of problems such as increased resistance and difficulty in mixing with the active material.

[0032] Due to the above D 50 The relationship between the volume cumulative particle size D when the cumulative volume of the solid electrolyte of the present invention is 10 volume % based on the laser diffraction scattering particle size distribution measurement method is 10 It is preferably 5.0 μm or less, particularly preferably 3.5 μm or less, and particularly preferably 2.0 μm or less. 10 For example, it is preferably 0.2 μm or more, particularly preferably 0.3 μm or more, and particularly preferably 0.4 μm or more.

[0033] In addition, the volume cumulative particle diameter D when the cumulative volume of the solid electrolyte of the present invention is 95 volume % based on the laser diffraction scattering particle size distribution measurement method is 95 It is preferably 40 μm or less, more preferably 30 μm or less, and particularly preferably 20 μm or less. 95 For example, it is preferably 1.5 μm or more, particularly preferably 2.0 μm or more, and particularly preferably 2.5 μm or more.

[0034] By calculating the volume cumulative particle size D 10 and D 95 The above range is preferred because it can sufficiently reduce the lattice distortion of the compound A contained in the solid electrolyte, suppress the increase in the surface area of ​​the entire solid electrolyte powder, and sufficiently improve the lithium ion conductivity of the solid electrolyte.

[0035] The solid electrolyte of the present invention is suitable for manufacturing by the following method. As raw materials, a lithium source compound, a phosphorus source compound, a sulfur source compound and a halogen source compound are used. As a lithium source compound, for example, lithium sulfide (Li2S) can be used. As a phosphorus source compound, for example, phosphorus pentasulfide (P2S5) can be used. As a sulfur source compound, when the lithium source compound and / or the phosphorus source compound is a sulfide, the sulfide can be used as a sulfur source compound. As a halogen source compound, a lithium halide can be used. These raw materials are mixed in such a way that the lithium element, the phosphorus element, the sulfur element and the halogen element reach a specified molar ratio. In addition, by calcining the mixed raw materials in an inert atmosphere or in an atmosphere containing hydrogen sulfide gas, a Li2O3 electrolyte can be obtained. a PS b X c Compound A is a crystalline phase represented by and having an argyrodite-type structure. As a method for increasing the argyrodite rate, one example is to increase the reactivity of the raw materials during roasting. Specifically, the following methods are mentioned: a method of crushing the lithium source compound, phosphorus source compound, sulfur source compound and halogen source compound to be the raw materials to the desired particle size; a method of uniformly mixing the raw materials; a method of roasting for a long time, etc. The atmosphere containing hydrogen sulfide gas can be 100% hydrogen sulfide gas, or it can be a mixed gas of hydrogen sulfide gas and an inert gas such as argon. The roasting temperature is, for example, preferably above 350°C and below 550°C. The holding time at this temperature is, for example, preferably above 0.5 hours and below 20 hours.

[0036] A solid electrolyte containing compound A is obtained by the above method. At this moment, the crystallinity of compound A contained in the solid electrolyte is high and the lattice distortion becomes low. However, since the particle size does not reach the expected value, it is necessary to adjust the particle size. For this reason, when a solid electrolyte is required to be pulverized, compound A sometimes produces lattice distortion due to the pulverization. Therefore, the research results of the inventors have made it clear that it is advantageous to pulverize the solid electrolyte under conditions that do not increase the lattice distortion.

[0037] The pulverization process can be carried out by wet or dry method. In order not to increase the lattice distortion, it is desirable to reduce the pulverization energy during the pulverization process. Specifically, it can be listed as: reducing the weight and / or number of the dispersion medium, reducing the peripheral speed and / or the processing time. In particular, the method for not increasing the lattice distortion is not limited to them. In the pulverization process, various medium mills can be used. As the medium mill, a ball mill, a bead mill, a paint stirrer, a homogenizer, etc. can be used. As the dispersion medium used in the medium mill, various ceramic balls and beads headed by aluminum oxide and zirconium oxide can be used. The diameter of the dispersion medium can be set to, for example, 0.1 mm or more and 50 mm or less.

[0038] When the pulverization treatment is performed by wet method, it is preferred to use an organic solvent as a dispersion medium from the viewpoint of being able to suppress the generation of hydrogen sulfide caused by the reaction between the solid electrolyte and water. As the organic solvent, for example, aromatic organic solvents such as toluene, xylene, benzene, and solvent naphtha; aliphatic organic solvents such as heptane, decane, n-hexane, cyclohexane, and mineral spirits can be listed. These organic solvents can be used alone or in combination of two or more.

[0039] The organic solvent is mixed with the solid electrolyte to form a slurry, and the slurry is subjected to wet grinding. From the viewpoint of suppressing the increase of the lattice distortion of compound A and easily obtaining a solid electrolyte with high lithium ion conductivity, the concentration of the solid electrolyte contained in the slurry is preferably set to, for example, 5% by mass or more and 50% by mass or less. In the wet grinding using a medium mill, with respect to the ratio of the dispersion medium to the slurry, from the viewpoint of being able to suppress the increase of the lattice distortion of compound A, it is preferred to use a dispersion medium of 5 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the slurry. From the viewpoint of being able to suppress the increase of the lattice distortion of compound A, it is preferred that the dispersion time based on the medium mill is generally set to 0.5 hours or more and 60 hours or less.

[0040] When wet pulverization is performed, from the viewpoint of improving the lithium ion conductivity of the solid electrolyte, it is preferred that the volume cumulative particle size D of the solid electrolyte after wet pulverization is 50The degree of pulverization is adjusted so as to preferably be 0.8 μm or more, more preferably be 0.9 μm or more, and further preferably be 1.0 μm or more so as not to increase lattice distortion.

[0041] The solid electrolyte of the present invention obtained in this way can be used as a material constituting a solid electrolyte layer, a material contained in an electrode mixture containing an active substance. Specifically, it can be used as a positive electrode mixture constituting a positive electrode layer containing a positive electrode active substance or a negative electrode mixture constituting a negative electrode layer containing a negative electrode active substance. Therefore, the solid electrolyte of the present invention can be used in a battery having a solid electrolyte layer, a so-called solid-state battery. More specifically, it can be used in a lithium solid-state battery. A lithium solid-state battery can be a primary battery or a secondary battery, and is preferably used in a lithium secondary battery. "Solid-state battery" means: in addition to a solid-state battery that does not contain a liquid substance or a gel-like substance as an electrolyte, it also includes, for example, a liquid substance or a gel-like substance containing less than 50% by mass, less than 30% by mass, or less than 10% by mass as an electrolyte.

[0042] The solid electrolyte layer in the solid-state battery can be manufactured by the following methods, etc.: for example, a method of dropping a slurry containing the solid electrolyte, binder and solvent of the present invention on a substrate and scraping it with a scraper or the like; a method of cutting the substrate with a scraper after contacting the slurry; a method of forming a coating film by screen printing, etc., and then removing the solvent by heating and drying. Alternatively, the powder of the solid electrolyte of the present invention can be pressed and then processed appropriately for manufacture. In addition to the solid electrolyte of the present invention, the solid electrolyte layer may also contain other solid electrolytes. The thickness of the solid electrolyte layer in the present invention is typically preferably 5 μm or more and 300 μm or less, and more preferably 10 μm or more and 100 μm or less.

[0043] From the viewpoint of improving lithium ion conductivity, the porosity of the solid electrolyte layer containing the solid electrolyte of the present invention is preferably 50% or less, more preferably 30% or less, and more preferably 20% or less. The porosity of the solid electrolyte layer can be adjusted, for example, by the pressing pressure when the solid electrolyte of the present invention in powder form is made into a powder compact. The aforementioned pressing pressure is preferably 20 MPa or more, for example.

[0044] The porosity can be calculated, for example, by the relationship shown below from the true density and apparent density of the solid electrolyte layer obtained by a liquid phase method (Archimedes method).

[0045] Void ratio (%) = (true density - apparent density) ÷ true density × 100

[0046] It should be noted that a mixture of the solid electrolyte of the present invention and other solid electrolytes can also be used as a solid electrolyte layer. When the solid electrolyte of the present invention is mixed with other solid electrolytes, the solid electrolyte of the present invention can also be used in combination with any of amorphous (glass), glass ceramics, and crystalline materials. When the other solid electrolyte mixed with the solid electrolyte of the present invention is a sulfide solid electrolyte, the sulfide solid electrolyte includes, specifically, Li2S-P2S5 system, Li4P2S6, Li7P3S 11 Etc. In addition, the solid electrolyte to be combined may be a non-sulfide, for example, an oxide-based solid electrolyte.

[0047] The solid-state battery preferably has a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, and the solid electrolyte layer contains the solid electrolyte of the present invention. Examples of the shape of the solid-state battery include a laminated type, a cylindrical type, and a square type.

[0048] The positive electrode mixture in the solid-state battery containing the solid electrolyte of the present invention contains a positive electrode active material. As the positive electrode active material, for example, a substance used as a positive electrode active material of a lithium secondary battery can be appropriately used. As the positive electrode active material, for example, spinel-type lithium transition metal compounds, lithium metal oxides with a layered structure, etc. can be listed. In addition to the positive electrode active material, the positive electrode mixture may also contain other materials headed by a conductive auxiliary agent.

[0049] The negative electrode mixture in the solid-state battery containing the solid electrolyte of the present invention contains a negative electrode active material. As the negative electrode active material, for example, a negative electrode mixture used as a negative electrode active material for a lithium secondary battery can be appropriately used. As the negative electrode active material, for example, carbon materials such as lithium metal, artificial graphite, natural graphite and difficult-graphitizable carbon (hard carbon), lithium titanate, titanium-niobium composite oxide, silicon, silicon compounds, tin and tin compounds can be listed. In addition to the negative electrode active material, the negative electrode mixture may also contain other materials headed by a conductive aid.

[0050] Example

[0051] Hereinafter, the present invention will be described in more detail by way of examples, but the scope of the present invention is not limited to these examples.

[0052] [Example 1]

[0053] To form Li 5.4 PS 4.4 Cl 0.8 Br 0.8Li2S powder, P2S5 powder, LiCl powder and LiBr powder are weighed in a manner. These powders are crushed and mixed using a ball mill to obtain a mixed powder. The mixed powder is calcined to obtain a calcined product containing lithium ion conductive sulfide. The calcination is carried out using a tubular electric furnace. During the calcination, 100% pure hydrogen sulfide gas is circulated into the electric furnace at 1.0 L / min. The calcination temperature is set to 450°C and the calcination takes 4 hours. The results of the XRD measurement confirm that the calcined product has a crystalline phase of argyrodite-type structure and LiCl 0.5 Br 0.5 composition.

[0054] The calcined product was roughly crushed with a mortar and pestle, and then crushed with a hammer crusher. The crushed product was mixed with a solvent to prepare a slurry with a concentration of 12% by mass. The slurry was supplied to a bead mill (zirconia beads with a diameter of 0.2 mm) for wet grinding. Toluene was used as the solvent of the slurry. After wet grinding, the slurry was subjected to solid-liquid separation to dry the solid component. The dried calcined product was sieved with a sieve with a mesh of 53 μm to obtain the target solid electrolyte.

[0055] [Example 2]

[0056] The calcination temperature, pulverization device, slurry concentration and medium diameter in Example 1 were changed to the values ​​shown in the following Table 1. Except for this, the same operation as in Example 1 was carried out to obtain a solid electrolyte.

[0057] [Example 3]

[0058] The calcination temperature and slurry concentration in Example 1 were changed to the values ​​shown in the following Table 1. Except for this, the same operation as in Example 1 was carried out to obtain a solid electrolyte.

[0059] [Example 4]

[0060] The calcination temperature, pulverization device, slurry concentration and medium diameter in Example 1 were changed to the values ​​shown in the following Table 1. Except for this, the same operation as in Example 1 was carried out to obtain a solid electrolyte.

[0061] [Comparative Example 1]

[0062] The calcination temperature, slurry concentration and medium diameter in Example 1 were changed to the values ​​shown in the following Table 1. Except for this, the same operation as in Example 1 was carried out to obtain a solid electrolyte.

[0063] [Comparative Example 2]

[0064] The slurry concentration and the medium diameter in Example 1 were changed to the values ​​shown in the following Table 1. Except for this, the same operation as in Example 1 was carried out to obtain a solid electrolyte.

[0065] 〔Evaluation 1〕

[0066] The argyrodite ratio was determined for the solid electrolytes obtained in the Examples and Comparative Examples by the following method. 5.4 PS 4.4 Cl 0.8 Br 0.8 Then, the D of the solid electrolyte is calculated. 10 , D 50 and D 95 The results are shown in Table 1 below.

[0067] [Determination of Argentum Rate]

[0068] The measurement was performed using SmartLab manufactured by Rigaku Corporation. The optical system was set to the focusing method, a Johnson-type monochromator was used on the incident side, and a D / teX Ultra 250 was used as the detector. A Soller slit of 5 degrees was used as the parallel slit between the incident side and the light receiving side. A stand not exposed to the atmosphere was used, the scanning axis was set to 2θ / θ, the scanning range was set to 20 degrees to 140 degrees, the step width was set to 0.01 degrees, and the scanning speed was set so that the maximum peak height became 10,000 Counts or more.

[0069] Furthermore, measurement was performed under the same conditions using SRM660a (compound name: LaB6) manufactured by NIST (National Institute of Standards and Technology) as a width standard.

[0070] The analysis used PDXL2 manufactured by Rigaku Corporation. The analysis steps are as follows. First, identification was performed. The CIF file (Crystallographic Information File) recorded below was read to determine the substance. The CIF file was obtained from ICSD (Inorganic Crystal Structure Database). Compound A used a CIF file with ICSD Collection Code of 418490. For heterogeneous phases, for example, in the case of lithium halides, a CIF file of 53818 was used, and the appropriate CIF file was used for identification until the unidentified peak disappeared.

[0071] Next, intensity decomposition was performed using WPPF. As a width correction, a width standard data file was selected. This file is equivalent to a file obtained by identifying the XRD data obtained by measuring SRM660a using LaB6, and analyzing and saving it using the same method as the analysis method shown below. A quantitative value was obtained from the analysis results, and the argyrodite rate was calculated.

[0072] 〔Analysis Method〕

[0073] Use an external standard sample to calibrate the angle and width of the peak. The model function of the peak shape uses the "split Pearson VII function". Then, from the "Basic" tab, select "Intensity Decomposition" in the "Precision Parameter Setting"-"Method". In addition, when lithium halide is included as a heterophase, the lattice constant changes due to the halogenation state. Therefore, the initial value of the lattice constant of the lithium halide is adjusted in a manner that the XRD data is roughly consistent with the calculated value. Then, precision is implemented. In precision, various parameters are adjusted until sufficient convergence. For example, the S value is based on 1.5 or less.

[0074] 〔Measurement of lattice distortion〕

[0075] The measurement and analysis were performed in the same manner as in [Measurement of Argentum Ratio], and the lattice distortion was calculated from the analysis results.

[0076] 〔D 10 , D 50 and D 95 Determination of

[0077] The sample (powder) was placed in an organic solvent using an automatic sample feeder for a laser diffraction particle size distribution measuring device (Microtrac SDC, manufactured by Microtrac-Bell). After irradiation with 30W ultrasonic waves for 60 seconds at a flow rate of 50%, the particle size distribution was measured using a laser diffraction particle size distribution measuring device "MT3000II" manufactured by Microtrac-Bell. The volume-based particle size distribution spectrum was used to measure D. 10 , D 50 and D 95 It should be noted that toluene was used as the organic solvent.

[0078] 〔Evaluation 2〕

[0079] The BET specific surface area and lithium ion conductivity of the solid electrolytes obtained in Examples and Comparative Examples were measured by the following method. The results are shown in Table 1 below.

[0080] [Measurement of BET specific surface area]

[0081] The sample (powder) was heated at 120°C for 1 hour in a vacuum using a pretreatment device "BELPREP-vacII" manufactured by Microtrac-Bell. Thereafter, the specific surface area was calculated from the nitrogen adsorption at liquid nitrogen temperature (77K) using a specific surface area measuring device "BELSORP-miniII" manufactured by Microtrac-Bell using the BET (Brunauer-Emmett-Teller) method.

[0082] 〔Determination of lithium ion conductivity〕

[0083] The solid electrolyte is uniaxially pressed in a glove box replaced with fully dry Ar gas (dew point below -60°C). Furthermore, a cold isostatic pressing device is used to form at 200MPa to produce pellets with a diameter of 10mm and a thickness of about 4mm to 5mm. After the carbon paste as an electrode is coated on the upper and lower surfaces of the pellets, a heat treatment is performed at 180°C for 30 minutes to prepare a sample for ion conductivity measurement. The lithium ion conductivity of the sample is measured using TOYO CORPORATION's Solartron 1255B. Under the conditions of a temperature of 25°C and a frequency of 0.1Hz to 1MHz, the formed sample is constrained with 6Ncm and measured using the AC impedance method.

[0084] [Table 1]

[0085]

[0086] As is clear from the results shown in Table 1, the solid electrolytes obtained in the examples have higher lithium ion conductivity than the solid electrolytes of the comparative examples.

[0087] Industrial Applicability

[0088] According to the present invention, a solid electrolyte having high lithium ion conductivity can be provided.

Claims

1. A solid electrolyte comprising the following compounds: The compound comprises a crystalline phase having an argyrodite-type crystal structure, and Li a PS b X c It indicates that, X is at least one halogen element, a represents a number of 3.0 to 6.0, b represents a number of 3.5 to 4.8, c represents a number of 0.1 to 3.0, The ratio of the crystalline phase having the argyrodite type crystal structure to the total crystalline phase constituting the solid electrolyte is 97 wt % or more, The compound has a lattice distortion of less than 0.10%, as determined by X-ray diffraction. 2 . The solid electrolyte according to claim 1 , which has a lithium ion conductivity of 4.0 mS / cm or more at 25° C.

3. An electrode mixture comprising the solid electrolyte according to claim 1 or 2 and an active material. A solid electrolyte layer comprising the solid electrolyte according to claim 1 or 2.

5. A solid-state battery comprising the solid electrolyte according to claim 1 or 2.

Citation Information

Patent Citations

  • Sulfide solid electrolyte

    JP2018029058A

  • Sulfide-Based Solid Electrolyte for Lithium Ion Batteries

    US20170222257A1